Introducing the Diversification of Fishery Products from Cultivated Milkfish as a Trigger for the Creative Economy in the Former Pros- titution Area of Kampung Dolly, Surabaya - Patmawati, Patmawati; Saputra, Eka Saputra; Sahidu, Adriana Monica; Samara, Syifania Hanidah; Leonard, Rikky; Agustina, Maulida; Rahmawati, Ghisella Ayu; A'yun, Shindy Novia; Ibrahimi, Zulfan; Husein, Mohamad Akmal Alwi (Journal of Aquaculture and Fish Health, 2024)
Kampung Dolly was originally the largest prostitution areain Southeast Asia which is associated with nightlife. On 19June 2014, a policy was issued by the Surabaya city govern-ment to close this prostitution area which abruptly causedmany people to lose their jobs that previously could obtain anoverall economic turnaround of over 300 million rupiah pernight. Even after a decade, the community still has not beenable to recover its economic independence. The research wasdeemed indispensable for assisting the community regain itseconomic strength. This activity was conducted by the lectur-ers and students of the Faculty of Fisheries and Marine Uni-versitas Airlangga to foster a creative economy in KampungDolly community by utilizing fishery resources for 41 partici-pants who were members of MSME N'Jarang Nambe, Kam-pung Dolly, Surabaya. Assistance and monitoring were alsoprovided to ensure a successful outcome for the participants.Preliminary questionnaires found that 87.8% of participantshad ever bought fisheries products and were knowledgeableabout various diversification product types available in themarket. The final questionnaires observed the participants'preferences on product packaging, marketing, and licensing oftheir products. A total of 54% of participants preferred simplepackaging with affordable pricing, 66% of participants wouldrather sell their product at conventional markets directly, andonly 37% of participants have applied for business permits. Inconclusion, this activity has successfully providedcomprehensive insight regarding the introduction of productdiversification and assistance during the production process totrigger the entrepreneurial spirit for regaining economicstability in Kampung Dolly communities.